The Influence of Promotion and Price on Purchase Decisions of Chicken Cuts Sellers - Mustari, Muh. Fiqri; Jumady, Edy; Rusni, Muh. (Journal La Bisecoman, 2025)
The influence of promotion and price on purchasing decisions at CV. Cahaya Huspi chicken sellers in Makassar, MUH. FIQRI MUSARI 2024. The purpose of this study was to determine the influence of promotion and price on purchasing decisions. The method used in this study was a survey method with a quantitative approach, namely by emphasizing hypothesis testing. The sample in this study were consumers who made purchases at Cahaya Huspi Makassar with a total of 97 participants from 161 questionnaires distributed. The sampling technique used the Accidental Sampling method by setting a time limit for distributing the questionnaire for two weeks. Data collection methods through questionnaires and direct observation. The data analysis used was descriptive quantitative using the SPSS program with a simple Linear Regression analysis method.